Pemilihan umum 1997 : perkiraan, harapan dan evaluasi - Kristiadi, J.; Legowo, T.A.; Budi Harjanto, N.T. (Jakarta : Centre for Strategic and International Studies, 1997)
Evaluation of the Indonesian 1997 general election
Errata slip inserted at end
Includes bibliographical references
Keywords: Elections -- Indonesia; Constitutional law -- Elections -- Indonesia